Growth and Production of Two Job’s Tears Cultivars (Coix Lacrima Jobi-L.) at Various Doses of NPK Compound Fertilizer (16:16:16) - Nugraha Ramadhan; Indra Dwipa (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2023)
Indonesia has the potential to develop alternative food sources, one of the cereal crops that has the potential and prospects to be developed is job's tears (Coix lacrima-jobi L.). Efforts that can be made to increase job's tears production are variety selection, proper cultivation techniques, and favorable environmental conditions. Fertilization is one of the most important factors that need to be considered in plant cultivation techniques. This research was conducted in Padang city, West Sumatera. The research was factorial in the form of a complete random design. The job’s tears cultivars used in this riset were Pulut and Batu. The purpose of this study was to determine the effect of NPK fertilizer on growth and yields of two job’s tears cultivars. NPK fertilizer dosage treatment in this study consisted of : 0 kg/hectare, 100 kg/hectare, 200 kg/hectare, and 300 kg/hectare. The results showed that there was no interaction between NPK fertilizer and two job’s tears cultivars. Pulut showed the highest mean values on growth variables (plant height, leaf length, and stem diameter), but Batu showed the highest mean values on yield variables (seed weight / plant). While the best dose of NPK fertilizer to increase growth and yield is 300 kg/hectare.